Speech-in-noise perception in unilateral hearing loss: Relation to pure-tone thresholds and brainstem plasticity. (28th July 2017) - Vannson, Nicolas; James, Chris J.; Fraysse, Bernard; Lescure, Boris; Strelnikov, Kuzma; Deguine, Olivier; Barone, Pascal; Marx, Mathieu
Abstract: We investigated speech recognition in noise in subjects with mild to profound levels of unilateral hearing loss. Thirty-five adults were evaluated using an adaptive signal-to-noise ratio (SNR50) sentence recognition threshold test in three spatial configurations. The results revealed a significant correlation between pure-tone average audiometric thresholds in the poorer ear and SNR thresholds in the two conditions where speech and noise were spatially separated: dichotic – with speech presented to the poorer ear and reverse dichotic – with speech presented to the better ear. This first result suggested that standard pure-tone air-conduction thresholds can be a reliable predictor of speech recognition in noise for binaural conditions. However, a subgroup of 14 subjects was found to have poorer-than-expected speech recognition scores, especially in the reverse dichotic listening condition. In this subgroup 9 subjects had been diagnosed with vestibular schwannoma at stage III or IV likely affecting the lower brainstem function. These subjects showed SNR thresholds in the reverse dichotic condition on average 4 dB poorer (higher) than for the other 21 normally-performing subjects. For the 7 of 9 subjects whose vestibular schwannoma was removed, the deficit was no longer apparent on average 5 months following the surgical procedure. These results suggest that following unilateral hearing loss the capacity to use monaural spectral information is supported by the lower brainstem. Highlights: Subjects with mild to total unilateral hearing loss were evaluated with both the Matrix test and clinical audiometries. Pure-tone air conduction can be a reliable predictor for binaural hearing evaluation. Vestibular schwannoma stage III or IV may affect the lower brainstem structure and creates binaural hearing distortions. A surgical schwannoma removal may allowed monaural spectral remapping.